Answer:
x = -4 thus negative
Step-by-step explanation:
Solve for x:
3 x + 12 = 0
Hint: | Isolate terms with x to the left hand side.
Subtract 12 from both sides:
3 x + (12 - 12) = -12
Hint: | Look for the difference of two identical terms.
12 - 12 = 0:
3 x = -12
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 3 x = -12 by 3:
(3 x)/3 = (-12)/3
Hint: | Any nonzero number divided by itself is one.
3/3 = 1:
x = (-12)/3
Hint: | In (-12)/3, divide 12 in the numerator by 3 in the denominator.
12/3 = (3×4)/3 = 4:
Answer: x = -4
What you want to do is take one of the 2 equations and isolate one variable. you will then use the value that you find for the variable and plug it back into the other equation. here is how:
This would be easiest to do with the second equation in the set since the x is not being multiplied by anything. So lets isolate the x in the second equation.
add 0.9y to both sides and you get:
x=4.5+0.9y
we now know what x is equal to in terms of y. so lets replace the x in the first equation with the new value. You get:
1.5(4.5+0.9y)-1.9y=-29
Now just solve for y:
6.75+1.35y-1.9y=-29
1.35y-1.9y=-35.75
-0.55y=-35.75
y=65
so now you know that y=65 so plug 65 in as y in the second equation to find x
x-0.9*65=4.5
Now simply solve for x
x-(-58.5)=4.5
x+58.5=4.5
x=-54
Hope this helped! :)
Answer:
+22
Step-by-step explanation:
Given g(x) = -x^2 + 4x - 11, g(4) is -(4)^2 + 4(4) - 11, or just -11.
Then -2 times g(4) = -2(-11) = +22
Answer:
-31
Step-by-step explanation:
-34 - -17 is actually -34 + 17, so you get -17. -17 - 14 = -31